Assessing cross-cultural validity of scales: a methodological review and illustrative example. - Beckstead JW; Yang C; Lengacher CA (International Journal of Nursing Studies, 2008)
In this article, we assessed the cross-cultural validity of the Women's Role Strain Inventory (WRSI), a multi-item instrument that assesses the degree of strain experienced by women who juggle the roles of working professional, student, wife and mother. Cross-cultural validity is evinced by demonstrating the measurement invariance of the WRSI. Measurement invariance is the extent to which items of multi-item scales function in the same way across different samples of respondents. We assessed measurement invariance by comparing a sample of working women in Taiwan with a similar sample from the United States. Structural equation models (SEMs) were employed to determine the invariance of the WRSI and to estimate the unique validity variance of its items. This article also provides nurse-researchers with the necessary underlying measurement theory and illustrates how SEMs may be applied to assess cross-cultural validity of instruments used in nursing research. Overall performance of the WRSI was acceptable but our analysis showed that some items did not display invariance properties across samples. Item analysis is presented and recommendations for improving the instrument are discussed.